THE EFFECT OF LEADERSHIP ON EMPLOYEE PERFORMANCE IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF KAMPAR REGENCY - Akbar Fauzi Sibarani; Zamhir Basem; Yulizar Yulizar (STIE Bangkinang Publishing, 2022)
This research was to determine the effect of leadership on employee performance at the Department of Population and Civil Registration of Kampar Regency. This analysis uses the independent variable, namely leadership. The dependent variable is performance. The sample of this study is all employees who work at the Department of Population and Civil Registration of Kampar Regency. Samples were conducted by purposive sampling method. The data was collected by using questionnaires distributed directly to employees as many as 31 questionnaires. The statistical method uses simple Linear Regression Analysis, by testing the hypothesis t statistical test. The results of this study indicate that leadership has a significant positive effect on employee performance, with a significant value less than 0.05. The contribution of the independent variable to the dependent variable is strong.